Instytucja wotum zaufania w świetle rozwiązań ustrojowych - Ruksza, Paweł (PRAWO i WIĘŹ, 2025)
The aim of the research is to evaluate the provisions on trust in the Constitution of the Republic of Poland and in local government. The vote of confidence, as an instrument of control, has been in local government since 2019. Despite the use of the same names of institutions with specific combined features, a vote of confidence in relation to is not the same as a vote of confidence in regard to existing devices in local government. It is a different institution with different applications and legal effects. The practice of using a vote of confidence in local government units states that this institution is mandatory.